2008
DOI: 10.1080/00952990802013664
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cortisol Secretion During Heroin Abstinence Is Elevated Only Nocturnally

Abstract: Several studies indicate abnormalities in the hypothalamic-pituitary-adrenal axis (HPA) during acute opiate withdrawal, but protracted withdrawal has gotten less study. The current study further characterized the 24-hour time course of plasma cortisol levels in heroin-dependent individuals who were abstinent for 10-15 days, which is beyond the 5 days of acute withdrawal, compared to demographically matched healthy controls using samples collected every 3 hours over 24 hours and assessed with radioimmunoassay (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…These findings stand in contrast to reports of higher cortisol levels in recently abstinent abusers of alcohol, opioids, and cocaine (7; 15; 16; 17). In a study of cocaine-dependent subjects, afternoon cortisol levels were elevated early in treatment, then returned to a baseline, similar to values in a control group, by the third week of abstinence (7).…”
Section: Discussioncontrasting
confidence: 99%
“…These findings stand in contrast to reports of higher cortisol levels in recently abstinent abusers of alcohol, opioids, and cocaine (7; 15; 16; 17). In a study of cocaine-dependent subjects, afternoon cortisol levels were elevated early in treatment, then returned to a baseline, similar to values in a control group, by the third week of abstinence (7).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, others have found that repeated precipitated withdrawal engages stress mechanisms including activation of the hypothalamic‐pituitary‐adrenal (HPA) axis that are not observed with spontaneous withdrawal in “drug‐dependent” mice . Indeed, salivary and serum cortisol levels are elevated in humans experiencing opioid detoxification, as well as in protracted withdrawal . Collectively, these findings suggest that repeated precipitated withdrawal using naloxone can significantly affect both behavior and physiology compared with morphine alone.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal HPA axis activity has been reported in post-dependent heroin addicts (58, 59). Recent clinical studies have shown that HPA activity and anxiety, but not negative mood ratings, could be normalized by opiate maintenance treatment, suggesting that depressive-like symptoms and basal HPA axis are not necessarily associated during abstinence (60).…”
Section: Discussionmentioning
confidence: 99%